How COVID-19 Affected Global Trade of Medical Products? - Movsisyan, Shushan (ՀՊՏՀ «Տնտեսագետ» հրատ․)
COVID-19 pandemic has become a real challenge to globalization and international economic relations. At the very onset of pandemic most countries have imposed trade restrictions to prevent the shortage of critical supplies. Even advanced integration units (European Union, EAEU etc.), where trade barriers were previously eliminated or reduced to a minimum, have not managed to give a coordinated response to a new situation. Most of these trade regulation measures apply to medical products required to combat the pandemic. The article studies trade policy changes during the pandemic and their impact on global trade of medical products. Կորոնավիրուսային համավարակն իսկական մարտահրավեր էր գլոբալացմանն ու միջազգային տնտեսական կապերին։ Համավարակի հենց սկզբում երկրների մեծ մասը առևտրի արգելքներ սահմանեց՝ ծայրահեղ անհրաժեշտ ապրանքների պակասուրդ թույլ չտալու համար։ Նույնիսկ ինտեգրացիոն կառույցները, որոնց ներսում մինչ այդ առևտրի խոչընդոտները հասցվել էին նվազագույնի, չկարողացան արձագանքել համակարգված ձևով։ Առևտրի կարգավորումների երկու երրորդը վերաբերում է բժշկական ապրանքներին։ Հոդվածում ուսումնասիրվել են կորոնավիրուսային համավարակի ընթացքում կիրառված առևտային կարգավորումներն ու դրանց ազդեցությունը բժշկական պարագաների համաշխարհային առևտրի վրա։ Пандемия коронавируса стала настоящим вызовом для глобализации и международных экономических отношений. В самом начале пандемии большинство стран ввели торговые ограничения для того, чтобы предотвратить дефицит важнейших товаров. Даже развитые интеграционные структуры, в рамках которых торговые барьеры ранее сводились к минимуму, не смогли скоординированно отреагировать на ситуацию. Примерно две трети торговых мер приходится на медицинские изделия. В статье исследуются торговые меры принятые во время пандемии, а также их влияние на мировую торговлю товарами медицинского назначения.
Keywords: Armenia and world